Shelf life responses of ‘Akito’ rose (Rosa spp.) cut flowers treated with growth regulator benzyl amino purine and microbiocide aluminium sulphate (International Journal of Agricultural Research, Innovation and Technology, 2020)
Rose (Rosa spp.) production for cut flowers is an integral part of the horticultural industry. However, because roses are exotic plants they exhibit serious problems related to poor climatic adaptation. A study was conducted at the School of Agricultural Sciences, University of Zambia to evaluate chemicals to extend flower shelf life. The cultivar ‘Akito’ was used as the test variety. Benzyl amino purine ([6- (benzylamino) purine]) (BAP), a growth regulator and aluminium sulphate (an acidifying reagent) were applied to cut flowers at 0, 5, 10, 15, and 20 mg L-l and 0, 400, 800 and 1200 mg L-l, concentration, respectively. BAP was applied to the plants in the greenhouse 2 days before harvest. A randomised complete block design arranged as a two- factor- factorial arrangement with three replications was used. Harvesting was done at the loose open calyx stage. Aluminium sulphate was applied to the holding solution where flowers were kept after harvest. The pH of the holding solution, blossoming (flower opening), leaf color of subtending leaves and bacterial population were monitored. The 400 mg L-l aluminium sulphate treatment caused an increase in acidity. There was concurrent decline in bacterial count in the first three days of application at less than 1 x 106 which was five times lower than the water control treatment. Bacterial population followed the trend of water acidity. The 20 mg L-l BAP application increased shelf life by 35 %. The results showed that BAP and aluminum sulphate treatment could enhance shelf life.Int. J. Agril. Res. Innov. Tech. 10(1): 6-12, June 2020